Visible-Light-Mediated Synthesis of Pyrazines from Vinyl Azides Utilizing a Photocascade Process - Hossain, Asik; Pagire, Santosh K.; Reiser, Oliver (Synlett, 2017)
A convenient method for the synthesis of substituted pyrazines from vinyl azides has been developed. This method is enabled by a dual-energy and electron-transfer strategy by visible-light photocatalysis. Initially, vinyl azides are activated by a triplet sensitization process from an excited ruthenium photocatalyst in the presence of water to form dihydropyrazines, followed by a single-electron-transfer (SET) process under oxygen (air) atmosphere that leads to the tetrasubstituted pyrazines in good to excellent yields.
Keywords: visible-light photocatalysis; pyrazines; synthetic methods; vinyl azides; photocascade process